ANALISIS PROYEKSI KETERSEDIAAN BERAS DI KABUPATEN BULUNGAN - Mohammad Wahyu Agang; Fikriyah Rosyidah (J-PEN Borneo : Jurnal Ilmu Pertanian, 2022)
ABSTRACTImplementation of the Bulungan Regency authorities software associated with meals safety withinside the shape of rice availability, it's miles was hoping that a quantitative plan will pass ahead through thinking about the influential parameters. The motive of this studies is to discover elements which have the capacity to be essential variables in leveraging manufacturing will increase due to which may be used as hints for hints for examples of sustainable rice availability regulations withinside the framework of saying rice availability in Bulungan Regency. The technique that may be used is to apply dynamic device modeling and projections to feature statistics into local making plans concerns if you want to declare the supply of rice in Bulungan Regency. The outcomes of the take a look at display a causal loop interplay such as a rice supply-call for device in Bulungan Regency which has reciprocal interactions among device members. The reciprocal courting among structures withinside the causal loop may be withinside the shape of positive (Surplus) or negative (Deficit) interactions. With an envisioned call for for rice in step with capita / yr of 92.383 kg, it's miles projected that the adequacy of rice in Bulungan Regency, primarily based totally on processed output, indicates that during 2020 the adequacy of rice represents a deficit of 238,383 kg, even as in 2021 to 2026 the adequacy of rice will enjoy a surplus. Key words: Rice, Food Security, System Dynamic. ABSTRAKImplementasi program pemerintah Kabupaten Bulungan terkait ketahanan pangan berupa ketersediaan beras, maka diharapkan suatu perencanaan bersifat kuantitatif dan bergerak maju menggunakan mempertimbangkan parameter-parameter yg berpengaruh. Tujuan berdasarkan penelitian ini merupakan buat mengidentifikasi faktor yg berpotensi menjadi variabel krusial pengungkit peningkatan produksi sebagai akibatnya bisa sebagai arahan rekomendasi contoh kebijakan ketersediaan beras berkelanjutan pada kerangka mengklaim ketersediaan beras pada Kabupaten Bulungan. Metode yg bisa dipakai merupakan menggunakan permodelan sistem dinamik proyeksi buat menambah keterangan menjadi pertimbangan perencanaan wilayah pada rangka mengklaim ketersediaan beras pada Kabupaten Bulungan. Hasil penelitian menampakan interaksi causal loop yg terdiri atas sistem kebutuhan-ketersediaan beras pada Kabupaten Bulungan yg mempunyai interaksi timbal pulang antar anggota sistem. Hubungan timbal pulang antar sistem pada causal loop bisa berupa interaksi positif (Surplus) atau negative (Defisit). Dengan perkiraan kebutuhan beras per kapita/tahun 92,dua kg maka diproyeksikan kecukupan beras pada Kabupaten Bulungan, berdasarkan output olahan mengambarkan bahwa Tahun 2020 kecukupan beras mengambarkan defisit sebanyak 238.383 kg, sedangkan tahun 2021 s/d 2026 kecukupan beras mengalami surplus.Kata kunci: Beras, Ketahanan Pangan, Sistem Dinamik